Performance of Gram Stains and 3 Culture Methods in the Analysis of Peritoneal Dialysis Fluid. Issue 2 (March 2019) - Buchanan, Ruaridh; Fan, Stanley; NicFhogartaigh, Caoimhe
Microbiological diagnosis of peritoneal dialysis (PD)-related peritonitis includes PD fluid cell count, Gram stain, and culture, as recommended by the International Society for Peritoneal Dialysis. In this retrospective study, we examined the utility of Gram stains and compared 3 culture methods. We examined a laboratory cohort (samples sent to the laboratory for any reason; n = 251) and a clinical cohort (samples sent from patients felt clinically to have peritonitis; n = 264). Culture positivity rates were higher in the clinical cohort (39.4%) than the laboratory cohort (21.5%), with no difference in the distribution of organisms between the cohorts; cell counts were significantly higher in culture-positive samples in both cohorts. Rates of positivity in the laboratory and clinical cohorts, respectively, were as follows: Gram stains 1.9% and 7.7%; direct plate culture 13% and 30.8% and "bedside" inoculated blood culture bottles 82.1% and 92.8%. Enrichment culture was never negative when another method was positive. Our data indicate that enrichment culture can be used as a single culture methodology for analyzing PD fluid without loss of sensitivity. They also suggest that Gram stains are of relatively low yield; consideration could be given to ceasing their routine performance provided that broad antimicrobial therapy is administered pending culture results.